SARS-CoV-2 spike protein S1 subunit induces pro-inflammatory responses via toll-like receptor 4 signaling in murine and human macrophages - Shirato, Ken; Kizaki, Takako (Heliyon, 2021)
Coronavirus disease 2019 (COVID-19), an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has now spread globally. Some patients develop severe complications including multiple organ failure. It has been suggested that excessive inflammation associated with the disease plays major role in the severity and mortality of COVID-19. To elucidate the inflammatory mechanisms involved in COVID-19, we examined the effects of SARS-CoV-2 spike protein S1 subunit (hereafter S1) on the pro-inflammatory responses in murine and human macrophages. Murine peritoneal exudate macrophages produced pro-inflammatory mediators in response to S1 exposure. Exposure to S1 also activated nuclear factor-κB (NF-κB) and c-Jun N-terminal kinase (JNK) signaling pathways. Pro-inflammatory cytokine induction by S1 was suppressed by selective inhibitors of NF-κB and JNK pathways. Treatment of murine peritoneal exudate macrophages and human THP-1 cell-derived macrophages with a toll-like receptor 4 (TLR4) antagonist attenuated pro-inflammatory cytokine induction and the activation of intracellular signaling by S1 and lipopolysaccharide. Similar results were obtained in experiments using TLR4 siRNA-transfected murine RAW264.7 macrophages. In contrast, TLR2 neutralizing antibodies could not abrogate the S1-induced pro-inflammatory cytokine induction in either RAW264.7 or THP-1 cell-derived macrophages. These results suggest that SARS-CoV-2 spike protein S1 subunit activates TLR4 signaling to induce pro-inflammatory responses in murine and human macrophages. Therefore, TLR4 signaling in macrophages may be a potential target for regulating excessive inflammation in COVID-19 patients. SARS-CoV-2, Spike protein, S1 subunit, Toll-like receptor 4, Inflammation, Macrophage